1979
DOI: 10.1080/15298667991429750
|View full text |Cite
|
Sign up to set email alerts
|

Drywall construction and asbestos exposure

Abstract: The rapid development of the drywall construction trade in the United States is described. It is estimated that some 75,000 U.S. construction workers are currently employed in this trade. The use of a variety of spackle and taping compounds is shown to be associated with significant asbestos exposure; air samples taken in the breathing zone by drywall tapers during sanding of taping compounds show fiber concentrations exceeding, by several times, the maximum level permitted by United States Government regulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 0 publications
1
30
0
Order By: Relevance
“…The asbestos ®ber concentrations generated by sanding were similar to those measured in the work environment of asbestos insulation workers who had a seven-fold increased risk of cancer of the lung and of the pleura . In a clinical report of drywall construction workers, radiological evidence of pulmonary asbestosis was observed in 40.9% of the workers examined; this compared to 48.5% among insulators [Fischbein et al, 1979]. Therefore, drywall tapers may have had asbestos exposure levels similar to those of insulators.…”
Section: Plasterersmentioning
confidence: 94%
See 2 more Smart Citations
“…The asbestos ®ber concentrations generated by sanding were similar to those measured in the work environment of asbestos insulation workers who had a seven-fold increased risk of cancer of the lung and of the pleura . In a clinical report of drywall construction workers, radiological evidence of pulmonary asbestosis was observed in 40.9% of the workers examined; this compared to 48.5% among insulators [Fischbein et al, 1979]. Therefore, drywall tapers may have had asbestos exposure levels similar to those of insulators.…”
Section: Plasterersmentioning
confidence: 94%
“…He showed that either chrysolite or amphibole asbestos, or both, were in spackling compounds, which could contain between 5±12% by weight of asbestos minerals. Fischbein et al [1979] found that 13 of the 15 industrial drywall taping and spackling compounds analyzed contained asbestos. Tapers spend up to 10% of their working time sanding dried spackle and could have experienced intermittent asbestos exposure through the 1960s.…”
Section: Plasterersmentioning
confidence: 98%
See 1 more Smart Citation
“…It is likely that the GWB in the two schools contained ACM joint compound, since the schools were built in the 1960s and that was the common method at the time of construction. (10) Because this study was released prior to the OSHA interpretation that GWB with greater than 1% asbestos in the joint compound was ACM, (11) the asbestos content of the joint compound was not reported.…”
Section: Introductionmentioning
confidence: 98%
“…Chrysotile‐containing joint compounds (i.e., calcium carbonate‐ or calcium sulfate‐based mixtures containing chrysotile fibers; JCC) are not currently manufactured in the United States, but were commonly used in drywall construction in the United States and elsewhere from the 1940s through the mid‐1970s. The magnitude of exposure to asbestos fibers from mixing, sanding, and cleanup of these joint compounds is difficult to reconstruct from the limited published data ( 1‐4 ) due to: (i) the absence of time‐activity information, (ii) the reporting of short‐term and/or peak fiber concentrations instead of preferred task or time‐weighted averages, ( 5 ) and (iii) the use of open‐face cassettes in proximity to emission sources, which may have captured nonrespirable particles that contained asbestos fibers. ( 6 ) In addition, sample preparation methods used at that time differ from current methods, and have been shown to increase fiber counts in joint‐compound dust relative to current methods.…”
Section: Introductionmentioning
confidence: 99%